Set up the equation and solve:
-27 = 8x - 5x (next simplify by subtracting 5x from 8x))
-27 = 3x (next divide both sides of the equation by 3)
-27/3 = 3x/3 (next simplify and solve)
-9 = x
Chat with our AI personalities
-27 = 3x-9 = x
Set up the equation and solve: -27 = 8x - 5x (next simplify by subtracting 5x from 8x)) -27 = 3x (next divide both sides of the equation by 3) -27/3 = 3x/3 (next simplify and solve) -9 = x
8x = 5x+24 8x-5x = 24 3x = 24 x = 8
Do you mean 6x+7x-8x if so it is 5x because 13x-8x = 5x
5x+49 = 8x+13 49-13 = 8x-5x 36 = 3x x = 12